Hubungan Parent Adolescent Relationship terhadap Risk Taking Behavior pada Remaja - Arfiani, Resfi Z; Utami, Rahayu Hardianti (Lembaga Yasin AlSys, 2024)
Risk-taking behavior refers to the tendency to engage in dangerous actions that could harm the individual. Meanwhile, parent-adolescent relationship refers to the interaction between parents and adolescents, encompassing closeness, communication, and comfort. This study aims to determine whether there is a relationship between parent-adolescent relationship and risk-taking behavior among adolescents. The research method used is quantitative with a correlational design. The population of this study consists of junior high school students in the city of Padang. The sample was selected using non-probability sampling, with a total of 408 participants. Data analysis was conducted using the Spearman correlation technique. The results show an r value of -0.774 with p = 0.000, indicating a significant negative relationship between parent-adolescent relationship and risk-taking behavior among adolescents in Padang. The implications of these findings suggest that emotional support and parental involvement play a crucial role in helping adolescents make wise decisions and avoid dangerous risks.